Glottic Squamous Cell Carcinoma Metastatic to the Brain - Patne, Shashikant CU; Pradhan, Satyajit; Mittal, Reena; Kumar, Mohan; Tanwar, Pranay (Asian Journal of Medical Sciences, 2013)
Spread of squamous cell carcinoma (SCC) commonly occurs vialocal lymphatic channels. Owing to scanty lymphatic drainage and vascular supply, SCC arising from the glottis rarely metastasizes. A 39-year-old male, operated for SCC of the glottis, presented 13 months later with complaints of headache. Computed tomography revealed a single ring-enhancing lesion in the right temporo-parietal region of the brain, suggestive of brain abscess. However, histopathological examination of the excised brain lesion showed metastasis of moderately differentiated SCC. Here, we report a rarecase of distant hematogenous brain metastasis of SCC of the glottis. DOI: http://dx.doi.org/10.3126/ajms.v5i1.5205 Asian Journal of Medical Science Vol.5(1) 2014 pp.77-80